Transcutaneous Auricular Vagus Nerve Stimulation Improves Spatial Working Memory in Healthy Young Adults - Sun, Jin-Bo; Cheng, Chen; Tian, Qian-Qian; Yuan, Hang; Yang, Xue-Juan; Deng, Hui; Guo, Xiao-Yu; Cui, Ya-Peng; Zhang, Meng-Kai; Yin, Zi-Xin; Wang, Cong; Qin, Wei (Frontiers in Neuroscience, 2021)
Working memory (WM) is one of the core components of higher cognitive functions. There exists debate regarding the extent to which current techniques can enhance human WM capacity. Here, we examined the WM modulation effects of a previously less studied techniques, transcutaneous auricular vagus nerve stimulation (taVNS). In Experiment 1, a within-subject study, we aimed to investigate whether and which stimulation protocols of taVNS can modulate spatial WM performance in healthy adults. Forty-eight participants performed baseline spatial n-back tasks (1, 3-back), then received online-taVNS, offline-taVNS or sham stimulation before or during (online group) the post-test of spatial n-back tasks in random order. Results showed that offline-taVNS could significantly increase hits in spatial 3-back task while no effect was found in online-taVNS or sham group. No significant taVNS effects were found on correct rejections or reaction time of accurate trails (aRT) in both online and offline protocols. To replicate the results found in Experiment 1 and further investigate the generalization effect of offline-taVNS, we carried out Experiment 2. Sixty participants were recruited and received offline-taVNS or offline earlobe stimulation in random order between baseline and post-tests of behavioral tests (spatial/digit 3-back tasks). Results replicated the findings, offline-taVNS could improve hits but not correct rejections or aRT in spatial WM performance, which were found in Experiment 1. However, there were no significant stimulation effects on digit 3-back task. Overall, the findings suggest that offline-taVNS has potential on modulating WM performance.